KNOWLEDGE AND ATTITUDE OF CLIMATE CHANGE ADAPTATION: THE VIEW OF MALAYSIAN UNIVERSITY STUDENTS - Baharudin, Rabeah Adawiyah; Sakawi, Zaini; Abdul Malek, Jalaluddin; Abas, Azlan (PLANNING MALAYSIA, 2024)
Sustainable consumption involves climate change adaptation. International organisations are emphasising and encouraging youth climate change preparation. This study examines undergraduate students' climate change adaptation knowledge and attitudes. A total of 384 undergraduate students from Universiti Malaya, Universiti Putra Malaysia, and Universiti Kebangsaan Malaysia responded to the survey. The findings showed a high level of knowledge and attitude among the students. The study also discovered significant and positive relationships between knowledge and attitude towards climate change. Furthermore, construct basic knowledge has a greater impact on climate change adaptation attitudes than risk perception. Their primary source of information is the internet. In light of these findings, internet information sources have an effect on students' knowledge and attitudes. This study provides an indicator of the youth's knowledge and attitude patterns, in order for policymakers and educational institutions to consider climate change adaptation more effectively.